Chitosan nanogels condensed to ferulic acid for the essential oil of Lippia origanoides Kunth encapsulation. (15th May 2018) - Almeida, Regiamara Ribeiro; Silva Damasceno, Elisa Tatiana; de Carvalho, Stephanne Yonara Barbosa; de Carvalho, Gustavo Senra Gonçalves; Gontijo, Leiriana Aparecida Pinto; de Lima Guimarães, Luiz Gustavo
Graphical abstract: Highlights: Chitosan linked to ferulic acid nanogels encapsulate essential oil. The ferulic acid content influences the nanogel encapsulation capacity. Morphological analysis shows how nanogels encapsulate the essential oil. Abstract: In order to enable the applicability of the essential oil of Lippia origanoides Kunth, increasing its stability and dispersion in aqueous base, were prepared nanogels of chitosan modified with ferulic acid to be used in their encapsulation. The results obtained by FTIR and 13 C SSNMR revealed the formation of CS-FA link in the different synthesized nanogels, while the studied by DLS showed particles with varied sizes and positive charge. A satisfactory encapsulation capacity of the essential oil was obtained for the nanogels. However, the nanogel synthesized with the highest proportion of ferulic acid in relation to chitosan 0.760 g of ferulic acid (CF1) showed the highest encapsulation efficiency of 20%. The results indicate the CF1 nanogel potential to encapsulate important components of the essential oil of L. origanoides, being able to guarantee the constituents, preservation, moreover facilitate the dispersion and release, expanding its use.